Situation Report: Poland, 21 May 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The May Anniversaries / by Janusz Bugajski Bishops Stand Firm but Adopt a Moderate Tone / by Ewa Chciuk Celt Fears for the Future of Private Farming in Poland / by Roman Stefanowski The Polish Socialist Youth Union Reviews Its Problems / by Janusz Bugajski Gorbachev in Poland for the Warsaw Pact Summit Meeting / by Anna Swidlicka Underground Video Tape Production / by Teresa Hanicka People in the News Bronislaw Geremek Dismissed from Academy of Science / by Janusz Bugajski Archbishop Henryk Gulbinowicz / by Anna Swidlicka Archbishop Andrzej Maria Deskur / by Anna Swidlicka Miscellaneous Items The Poor State of Electrification in the Countryside / by Roman Stefanowski Obsolescence in the Paper Industry / by Roman Stefanowski Serious Shortage of Drugs Reported / by Roman Stefanowski